PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL KOOPERATIF TIPE TPS DI KELAS V SEKOLAH DASAR - Yuliana, Adisti; Bistari, Bistari; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This study aims to describe the increase in student learning outcomes in mathematics learning using a cooperative model of type think pair share in class V students of Primary School 40 North Pontianak. The research method used is descriptive method of classroom action research and collaborative nature. The research subjects included teachers and students of VB grade at Negeri Pontianak 40 North Elementary School with 18 students. Data collection techniques used are direct observation techniques and measurement techniques with data collection tools, namely the teacher assessment instrument sheet planning learning, the instrument assessment instrument teacher's ability to carry out learning, and documents student learning outcomes. The results of the study showed an increase in the ability of teachers to plan learning with an average of 3.17 cycles I to 3.65 cycles II. The results of the study showed an increase in the ability of teachers to carry out learning with an average of 3.08 first cycle to 3.76 second cycle. The average student learning outcomes increased from 63.42 cycle I to 79.44 cycle II. Thus the study using a cooperative model of think pair share type in mathematics learning in class V of Elementary School 40 North Pontianak can improve student learning outcomes. Keywords: Classroom Action Research, Learning Outcomes, TPS Type Coopertive Model